Fiscal Policies to Address Climate Change in Asia and the Pacific - Dabla-Norris, Era (Washington, D.C International Monetary Fund (IMF), 2021)
Climate change is one of the greatest challenges facing policymakers worldwide, and the stakes are particularly high for Asia and the Pacific. This paper analyzes how fiscal policy can address challenges from climate change in Asia and the Pacific. It aims to answer how policymakers can best promote mitigation, adaptation, and the transition to a low-carbon economy, emphasizing the economic and social implications of reforms, potential policy trade-offs, and country circumstances. The recommendations are grounded in quantitative analysis using country-specific estimates, and granular household, industry, and firm-level data. (IMF page)
​Executive Summary and Policy Implications -- 1. Climate Change in Asia and the Pacific: Stylized Facts -- 2. How to Accelerate Mitigation Efforts in Asia and the Pacific -- 3. Compensating Households, Industries, and Firms for Higher Carbon Prices -- 4. Adaptation Challenges in Asia and the Pacific -- 5. Supporting Green Investment and Promoting a Green Recovery
At head of title: Asia and Pacific Department ; Fiscal Affairs Department
Includes bibliographical references (P: 97-105).
Keywords: Social problems and services; CLIMATIC CHANGE; ENVIRONMENTAL PROBLEMS; FISCAL POLICY; ADAPTATION TO CHANGE; ASIA AND THE PACIFIC